Islamic Republic of Iran : 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Islamic Republic of Iran. (IMF Staff Country Reports; Country Report, 2008)
The Islamic Republic of Iran's 2008 Article IV Consultation underlies that the economy is showing signs of overheating owing to high oil prices and a significant policy stimulus. IMF policy advice has focused on measures to reduce inflation and structural reforms aimed at stimulating growth and employment creation. Consistent with IMF recommendations, in 2007/08, the authorities reduced the non-oil fiscal deficit, contained energy subsidies, improved revenue administration, and intensified their efforts to bring banking supervision closer to international standards.